"Becoming a Sage" in the locale: The case of 17th-century northern scholar Yan Yuan. Issue 3 (3rd July 2022) - Dongjie, Wang
Abstract: From the mid-Ming period on, the idea of becoming a "sage" became an intellectual trend in society. However, the experience of Hebei-based early-Qing scholar Yan Yuan (顏元, 1635–1704) and his peers shows that, unlike the situation described in many studies as "everyone becoming sages, " most people at the time were not interested in being sages, and many with those aspirations were not supported by their social groups. In fact, "education" was not a one-way flow from elites to the masses. The impact of the masses on the elite cannot be ignored. Yan Yuan had to gradually adjust his mode of operation. Furthermore, the folklore surrounding Yan Yuan shows how ordinary people redefined the meaning of "sage" and redrew the relationship between "influencer" and "the influenced."